2020
DOI: 10.3803/enm.2020.871
|View full text |Cite
|
Sign up to set email alerts
|

Variabilities in Weight and Waist Circumference and Risk of Myocardial Infarction, Stroke, and Mortality: A Nationwide Cohort Study

Abstract: Background: Evidence regarding the association between variabilities in obesity measures and health outcomes is limited. We aimed to examine the association between variabilities in obesity measures and cardiovascular outcomes and all-cause mortality.Methods: We identified 4,244,460 individuals who underwent health examination conducted by the Korean National Health Insurance Service during 2012, with ≥3 anthropometric measurements between 2009 and 2012. Variabilities in body weight (BW) and waist circumferenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…Another longitudinal study of 4.4 years in 16,095 cases of myocardial infarction, 18,957 cases of stroke, and 30,200 cases of all-cause deaths demonstrated that increased variability of body weight and WC was associated with high risk for all three outcomes. These findings suggested that a variable, instead of a relatively stable body weight, either high or low, was associated with adverse prognosis [ 43 ]. A post-hoc breakdown of the SYNTAX Extended Survival study in patients with left main coronary artery disease that was revascularized either with coronary artery bypass surgery or percutaneous coronary intervention, showed that patients with either low baseline BMI and low WC, or low BMI/high WC, or high BMI/high WC, exhibited higher 10-year mortality risk compared to patients with high BMI/low WC.…”
Section: Discussionmentioning
confidence: 99%
“…Another longitudinal study of 4.4 years in 16,095 cases of myocardial infarction, 18,957 cases of stroke, and 30,200 cases of all-cause deaths demonstrated that increased variability of body weight and WC was associated with high risk for all three outcomes. These findings suggested that a variable, instead of a relatively stable body weight, either high or low, was associated with adverse prognosis [ 43 ]. A post-hoc breakdown of the SYNTAX Extended Survival study in patients with left main coronary artery disease that was revascularized either with coronary artery bypass surgery or percutaneous coronary intervention, showed that patients with either low baseline BMI and low WC, or low BMI/high WC, or high BMI/high WC, exhibited higher 10-year mortality risk compared to patients with high BMI/low WC.…”
Section: Discussionmentioning
confidence: 99%
“…The Framingham Heart Study reported increased mortality and morbidity due to coronary heart disease in subjects with highly variable body weights [ 12 ]. In a Korean nationwide cohort study, high variabilities in body weight were associated with higher risks of cardiovascular disease and all-cause mortality [ 22 ]. We provided evidence that weight cycling was associated with the development of diabetes [ 23 ], and the findings of the present study are in line with the results of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…The uncorrected VIM was corrected using this formula: (VIM uncorrected×mean of CV)/mean of VIM uncorrected [ 26 ]. Because the results from all variability measures were similar (with exception of the results between variability measures and the relationship with retinopathy in our primary analysis), the corrected variability independent of the mean (cVIM) was used as the primary variability measure in this study whiles results from the other variability measures are reported for comparative purposes [ 16 , 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%